Informing the decision-making process for potential PMT/vPvM chemicals through the adoption of a risk-based prioritization framework: the ZeroPM approach - Todd Gouin; Annette Bitsch; Majorie van Duursen; Sylvia E. Escher; Timo Hamers (Environmental Sciences Europe)
Abstract A risk-based strategy is presented aimed at prioritizing chemicals screened as potential persistent, mobile and toxic (PMT) or very persistent and very mobile (vPvM) substances. Prioritization is done to strengthen the decision-making process regarding actions that might be taken against chemicals screened as potential PMT/vPvM substances. Such actions can range from acquiring additional data aimed at reducing uncertainties in toxicological effect concentrations or internal exposure concentrations to—in case of acceptable uncertainty—suggesting compounds for prevention and/or removal measures in order to limit future exposure. The prioritization strategy is developed within the ZeroPM project and applies a variety of tools, including in silico and in vitro models for exposure and toxicity hazard assessment. These tools will be applied to chemicals identified as PMT/vPvM substances, with a preliminary emphasis on substances belonging to three chemical classes, i.e. perfluorinated compounds, triazines and triazoles. Here we describe the ZeroPM approach providing a proof-of-principle illustrative example, based on data-rich substances, results from which demonstrate how prioritization can be achieved using a risk-based approach that uses data obtained from new approach methodologies (NAMs) and environmental exposure concentrations, obtained either through modelling or monitoring studies. Results are communicated using a risk-based prioritization matrix, which can be used to help to communicate prioritization needs, such as identifying data gaps or for guiding actions aimed at mitigating exposure. The precision and accuracy of the prioritization matrix is evaluated using several data-rich chemicals, which identifies perfluorooctanoic acid and perfluorooctane sulfonic acid as high priority, due to a combination of toxicity and exposure estimates, whereas atrazine and melamine are observed at lower priority. The proposed risk-based prioritization framework thus represents a complementary source of information that should help support regulatory decision-making for PMT/vPvM substances.